FRI0117 Chronological changes in achieving j-haq remission in patients with early-stage rheumatoid arthritis in the iorra cohort. (15th June 2017) - Ochiai, M; Tanaka, E; Inoue, E; Yamaguchi, R; Shimizu, Y; Sugimoto, N; Ikari, K; Nakajima, A; Taniguchi, A; Yamanaka, H
Abstract : Background: With the introduction of biologic disease-modifying antirheumatic drugs (DMARDs) and the increase in the approved maximum dose of methotrexate in our country, the treatment of rheumatoid arthritis (RA) has advanced dramatically in the past 2 decades. Consequently, many patients were able to achieve clinical remission and low radiographic progression rates 1–3 . In view of these dramatic changes in RA treatment, we investigated whether the Japanese version of the Health Assessment Questionnaire (J-HAQ) improved chronologically due to improved treatment over time. Objectives: To investigate chronological changes in achieving J-HAQ remission and the factors related to J-HAQ remission in Japanese patients with an early stage of RA. Methods: RA patients who enrolled in the IORRA cohort for the first time between 2000–2002 (Term 1), 2005–2007 (Term 2), and 2010–2012 (Term 3) and were within 2 years of disease onset were examined. For each patient in Term 3, one patient was extracted from Term 1 and Term 2 by matching the sex, age, and J-HAQ score. Among them, patients with J-HAQ >0.5 at study entry (baseline) were selected; the time to achieve J-HAQ remission (J-HAQ ≦0.5) and the J-HAQ remission rate at 3 years were analyzed. Multivariate analysis was performed to assess factors related to achieving J-HAQ remission. Results: In each term, 348 RA patients were extracted. At baseline, the average J-HAQ of all 1, 044 patients was 0.52. Baseline characteristics of 408 patients with baseline J-HAQ >0.5 were as follows: female, 89.0%; mean age, 56.3 years; anti-cyclic citrullinated peptide (anti-CCP) antibody positivity, 78.0%; mean Disease Activity Score with 28-joint count (DAS28), 4.37; and mean J-HAQ, 1.11. The mean time from baseline to achieving J-HAQ remission became significantly shorter chronologically (Term 1: 2.2 years; Term 2: 1.8 years; Term 3: 1.7 years; p<0.005, Fig.1 ). J-HAQ remission rates significantly increased in both Term 2 (55.2%) and Term 3 (57.4%) compared with Term 1 (37.5%; p<0.005). The factors significantly related to achieving J-HAQ remission at 3 years were younger age (OR 1.02; 95% CI 1.00–1.04) and enrollment in Term 2 (OR 2.0; 95% CI 1.2–3.5) or Term 3 (OR 2.3; 95% CI 1.3–4.1) compared with enrollment in Term 1. Conclusions: Along with the improvement in RA treatment, patients were able to achieve J-HAQ remission more frequently and more quickly. References: Mod Rheumatol. 2007;17:283–9.2) J Rheumatol. 2015; 42:2279–87.3) Rheumatology. 2016;55:1053–1065. Disclosure of Interest: M. Ochiai: None declared, E. Tanaka Consultant for: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Pfizer, Takeda Pharmaceutical, and Ayumi Pharmaceutical., Speakers bureau: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Pfizer, Takeda Pharmaceutical, and Ayumi Pharmaceutical., E. Inoue: None declared, R. Yamaguchi: None declared, Y. Shimizu: None declared, N. Sugimoto Speakers bureau: Takeda Pharmaceutical and Bristol Myers Squibb., K. Ikari Grant/research support from: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., Speakers bureau: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., A. Nakajima Consultant for: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company, Speakers bureau: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company, A. Taniguchi Grant/research support from: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., Speakers bureau: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., H. Yamanaka Grant/research support from: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Consultant for: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Speakers bureau: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers.